Concurrent analysis of hospital stay durations and mortality of emerging severe acute respiratory coronavirus virus 2 (SARS-CoV-2) variants using real-time electronic health record data at a large German university hospital. Issue 1 (4th May 2023) - Hazard, Derek Y.; Grodd, Marlon; Makoudjou, Adeline; Lozano, Sara; Prunotto, Andrea; Tippmann, Patric; Zöller, Daniela; Mathé, Philipp; Rieg, Siegbert; Wolkewitz, Martin
Abstract: Multistate methodology proves effective in analyzing hospitalized coronavirus disease 2019 (COVID-19) patients with emerging variants in real time. An analysis of 2, 548 admissions in Freiburg, Germany, showed reduced severity over time in terms of shorter hospital stays and higher discharge rates when comparing more recent phases with earlier phases of the pandemic.